A Tyrosine-Hydroxylase Characterization of Dopaminergic Neurons in the Honey Bee Brain - Tedjakumala, Stevanus R.; Rouquette, Jacques; Boizeau, Marie-Laure; Mesce, Karen A.; Hotier, Lucie; Massou, Isabelle; Giurfa, Martin (Frontiers in Systems Neuroscience, 2017)
Dopamine (DA) plays a fundamental role in insect behavior as it acts both as a general modulator of behavior and as a value system in associative learning where it mediates the reinforcing properties of unconditioned stimuli. Here we aimed at characterizing the dopaminergic neurons in the central nervous system of the honey bee, an insect that serves as an established model for the study of learning and memory. We used tyrosine hydroxylase (TH) immunoreactivity (ir) to ensure that the neurons detected synthesize DA endogenously. We found three main dopaminergic clusters, C1 to C3, which had been previously described; the C1 cluster is located in a small region adjacent to the esophagus and the antennal lobe; the C2 cluster is situated above the C1 cluster, between the antennal lobe and the vertical lobe of the mushroom body; the C3 cluster is located below the calyces of the mushroom body. In addition, we found a novel dopaminergic cluster, C4, located above the dorsomedial border of the lobula, which innervates the visual neuropils of the bee brain. Additional smaller processes and clusters were found and are described. The profuse dopaminergic innervation of the entire bee brain and the specific connectivity of DA neurons, with visual, olfactory and gustatory circuits, provide a foundation for a deeper understanding of how these sensory modules are modulated by DA, and the DA-dependent value-based associations that occur during associative learning.